DEVELOPING INSTRUCTIONAL DESIGN FOR TEACHING WRITING PROCEDURAL TEXT USING PROJECT BASED LEARNING - bani, Nur; Sutapa, Yohanes Gatot; Sada, Clarry (English Language Education Study Program, 2021)
This research was aimed to develop an Intructional design in teaching procedural text using project based learning. The instructional design assisted for teaching writing for ninth grade students at SMP Negeri 2 Pontianak. This research applied development research and ADD procedure. On the analysis stage the researcher found the fundamental problems and needs of the students as well as the teacher expectation of writing material. On the designing and developing stage, the researcher collected the sources that needed and developed the instructional design. After the product assessed by the material expert, the instructional design considered as valid and applicable to use. The researcher hope that, this product can be applied in the classroom. As for the future research, the researcher suggested to conduct the instructional design based on the needs of the students. Drawing a clear design is needed to lead a good development of product.